2017
DOI: 10.1016/j.psi.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

¿Dejaría a mi pareja? Influencia de la gravedad de la transgresión, la satisfacción y el compromiso en la toma de decisión

Abstract: Dejar una relación de pareja es una de las decisiones más difíciles que las personas tienen que tomar, en ocasiones, en algún momento de su vida. Esta investigación pretende contribuir a la comprensión del proceso implicado en esta toma de decisión a través de 2 estudios. En el primero participaron 265 personas de población general, examinándose los diferentes tipos de transgresiones (conflictos) que llevarían a las personas a dejar la relación, la gravedad y las diferencias de género en dichas transgresiones.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
1
17
0
3
Order By: Relevance
“…used to enforce sexual violence, given that it is in these situations that relational factors play a major role in the decision making process (e.g., Garrido-Macías et al, 2017).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…used to enforce sexual violence, given that it is in these situations that relational factors play a major role in the decision making process (e.g., Garrido-Macías et al, 2017).…”
Section: Article In Pressmentioning
confidence: 99%
“…Finally, results showed that the influence of dependence on the maintenance of an abusive relationship occurs only when the type of tactic used is less severe (positive verbal sexual coercion or coaxing). Thus, it seems clear that the risk factors have greater impact when deciding whether to maintain or leave an abusive relationship when the man adopts subtle tactics of sexual violence in order to have sex (e.g., Garrido-Macías et al, 2017).…”
Section: Article In Pressmentioning
confidence: 99%
“…Finally, consistent with Hypothesis 1d, the results indicated the absence of gender differences in the use of the exit response, or abandoning the relationship. Therefore, according to the previous literature, exit responses could be primed by other factors with a relational or situational nature such as commitment to the relationship or people's perception of the seriousness that could arise from the conflict's consequences (Beltrán-Morillas, Valor-Segura, & Expósito, 2015;Garrido-Macías et al, 2017;Holt & DeVore, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, regarding participants' characteristics, their educational level is a variable that needs to be considered given that the educational level could correlate positively with EI (Goldenberg, Matheson, & Mantler, 2006) and adaptive marital conflict management (Gherghinescu & Gl veanu, 2015). With regard to situational characteristics taken into account, variables such as the frequency and the severity of the conflicts may be necessary because they could influence the type of responses that people will adopt (Garrido-Macías et al, 2017). Third, although the use of self-report measures has a strong external validity, they are based on subjective perceptions of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships are an important source of well-being and happiness (Centro de Investigaciones Sociológicas, 2010). However, when the relationship is conflicting and violent, it could become one of the main causes of suffering (Garrido-Macías, Valor-Segura, & Expósito, 2017;Valor-Segura, Expósito, Moya, & Kluwer, 2014). The inability to properly confront this situation could affect different psychosocial areas such as self-esteem, loneliness, social support, and life satisfaction (Gómez-Franco & Sendín, 2014).…”
Section: Controlling Behaviors Through New Technologiesmentioning
confidence: 99%